About The Increase Of Reproductive Types In The Development Cycle - Begali Xoliqnazarov (Genius Journals, 2022)
Ontogeny lasts longer than the developmental cycle. The length of an animal or plant development (life) cycle is determined by the number of generations (generation) in a year or the number of past spring (years) for one generation. The process also includes forced peace and pauses. This article discusses the multiplication of reproductive species in the development cycle.
Keywords: ontogeny; development cycle; metagenesis; heterogeneity